Evaluation of Mckinsey 7s Framework Model Approach to Credit Distribution With 5C and 7P Principles at Commercial Banking - Gina Rahmasari; Martha Fani Cahyandito; Agust Tato (International Journal of Social Service and Research, 2022)
The strategic management process in lending is carried out starting from environmental analysis when determining market targets and credit risk assessments, then formulating strategies in lending by applying the principle of prudence in each credit process which then implementing the strategy can be seen from the NPL ratio, and the last process is an evaluation of the implementation of the 5C and 7P principles on lending at the Commercial Banking Directorate of PT Bank Mandiri (Persero) Tbk. The study aims to find out the implementation of the 5C and 7P principles. This study uses descriptive methods to identify problems, explain symptoms, and examine conditions and prevailing practices based on the information collected. Moreover, based on the explanation, from each item of the questionnaire, it can be concluded that the application of the 5C and 7P principles to credit distribution at Bank Mandiri is quite good, but it is necessary to pay attention to several subvariables, especially personality on the 7P principle, profitability on the 7P principle, and the Bank's profitability.